Systematic screening and focused evaluation for veno-occlusive disease/sinusoidal obstructive syndrome (VOD/SOS) following allogeneic stem cell transplant is associated with earlier diagnosis and prompt institution of defibrotide treatment - Avenoso, Daniele; Kenyon, Michelle; Mehra, Varun; Krishnamurthy, Pramila; Kulasekararaj, Austin; Gandhi, Shreyans; Dazzi, Francesco; Naresh Shah, Mili; Wood, Henry; Leung, Ye Ting; Eaton, Alicia; Anteh, Sandra; et al. (Frontiers in Transplantation, 2022)
Sinusoidal obstructive syndrome (SOS), also known as hepatic veno-occlusive disease (VOD), is a potentially life-threatening complication following haemopoietic stem cell transplantation (HSCT). The availability of new drugs for malignant hematological conditions has allowed more patients to be eligible for allogeneic haematopoietic stem cell transplants, which has translated into a significant proportion of transplant patients having multiple risk factors for VOD/SOS. Based on these considerations, we undertook a dedicated weekly VOD/SOS ward round, aiming to facilitate early diagnosis of VOD/SOS and pre-emptively identify patients at risk, where a careful evaluation of differential diagnosis is essential. Herein, we present the results of our VOD/SOS ward round; between September 2020 and April 2022, 110 consecutive patients were evaluated in a focused VOD/SOS ward round. From the 110 patients, 108 had undergone HSCT and had at least one known risk factor for developing VOD/SOS. The median number of risk factors present in the VOD/SOS group and non-VOD/SOS group was five (range: three to six) and three (range: zero to seven), respectively. Late-onset VOD/SOS was diagnosed in 45% of our patients. The early identification of patients with multiple risk factors for VOD/SOS allowed an earlier diagnosis and the administration of defibrotide on the same day of diagnosis, which was two days earlier than our previous experience prior to the implementation of this protocol.